Chudley–McCullough Syndrome: Case Report and the Role of Neuroimaging to Suggest the Diagnosis - Freitas, Leonardo Furtado; Barros, Gabriel Santaterra; Barletta, Enrico Affonso; de Araújo Coimbra, Pablo Picasso; Lourenço, Charles Marques; Ferreira, Paula Mendes (Journal of Pediatric Neurology, 2021)
Chudley–McCullough syndrome (CMS) is an autosomal recessive condition first described in 1997. The most striking features of this syndrome include sensorineural hearing loss, craniofacial disproportion, and brain abnormalities such as agenesis of the corpus callosum, polymicrogyria, ventriculomegaly, and changes in cerebellar architecture. We described the case of a 2-year-old male child patient with CMS confirmed by genetic testing (GPSM2 gene mutation), who presented with global developmental delays and characteristic neuroimaging features including arachnoid cysts, agenesis of the corpus callosum, cerebellar dysplasia, and frontal heterotopia. Early recognition of this rare clinical syndrome may reduce the diagnostic odyssey and ultimately improve the quality of life for affected children. This report will focus on unique clinical and radiographic features of CMS.
Keywords: Chudley–McCullough syndrome; genetic syndrome; neuroradiology